PROBLEMS OF THE ORGANIZATION OF PREGRAVID PREPARATION AND MANAGEMENT OF PREGNANCY IN WOMEN WITH RECURRENT MISCARRIAGE IN THE STRUCTURE OF PRIMARY HEALTH CARE - E. A. Vartanyan; O. V. Gridnev; A. V. Belostotskiy; E. V. Pesennikova (Исследования и практика в медицине, 2016)
Purpose. Assessment of the scope and coverage of the surveys of patients with recurrent pregnancy losses in primary care of Zelenograd administrative district of Moscow.Materials and methods. Comparison of the frequency of occurrence of miscarriage in Europe, USA, Russia and in Moscow has been held. They performed a retrospective analysis of 221 history for the period 2013–2015 in patients with a history of 2 or more cases of miscarriage. The selection criteria for the study were: completion of pregnancy at term of gestation from 22 to 37 weeks, presence of a diagnosis of “habitual miscarriage” at statement on the account of pregnancy.Results. The factors predisposing to miscarriage are described, the coverage of the primary care of these patients, timeliness of registration of pregnancy, the completeness of the survey related professionals if patients ‘ comorbidity are estimated. The estimation of the frequency of occurrence of extragenital somatic pathology in patients with HM and the impact of this disease on pregnancy is held. The influence of previously deferred inflammatory diseases of the pelvic organs on a probable miscarriage is estimated, the evaluation of the quality of diagnosis of such diseases at an early stage of monitoring in primary care is held. It is established that pregravid preparation of patients with HM in 80% can be made in surveys provided by the territorial program of medical service. They evaluated the role of costly research conducted in the framework of pregravid training in patients with HM and the feasibility of conducting of these studies.Conclusion. The recommendations for the prevention of a probable miscarriage and the principles of monitoring of these patients in primary care on the example of Zelenograd administrative district basis are developed, the proposal for the introduction of these techniques in primary health care is formulated.